2020
DOI: 10.3390/pr8070844
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Characterization Studies of CoO/Co3O4 Nanocomposite

Abstract: CoO/Co3O4 nanoparticles (NPs) were synthesized by using a fresh egg white-assisted combustion method which acts as a new approach for green synthesis of this composite. This method was carried out by the direct heat of cobalt precursor with egg white at low temperature for very short period. In fact, this route is a novel, cheap and appropriate technique yielding nanoparticle-based materials. CoO/Co3O4 nanoparticles were characterized by examining the structure and identifying the elements and determining the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 50 publications
(47 reference statements)
5
35
0
Order By: Relevance
“…However, it contains high concentrations of both amino acids and proteins, such as albumen and lysozyme [33]. These constituents can act as reducing, capping, and stabilizing agents in the preparation of nanomaterials [34]. In addition, egg white plays a controlling role in the shape of the prepared nano system [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, it contains high concentrations of both amino acids and proteins, such as albumen and lysozyme [33]. These constituents can act as reducing, capping, and stabilizing agents in the preparation of nanomaterials [34]. In addition, egg white plays a controlling role in the shape of the prepared nano system [35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the investigated system has superparamagnetism properties depending on its nano particle nature. Moreover, the squareness of the prepared Cu 1.5 Mn 1.5 O 4 NPs was below 0.5, indicating a decrease in anisotropy in the crystal lattice [27]. This behavior could be attributed to magnetostatic interaction between these particles [27].…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, the squareness of the prepared Cu 1.5 Mn 1.5 O 4 NPs was below 0.5, indicating a decrease in anisotropy in the crystal lattice [27]. This behavior could be attributed to magnetostatic interaction between these particles [27]. Therefore, the prepared Cu 1.5 Mn 1.5 O 4 system can be used in the manufacture of spintronic devices depending upon its room temperature ferromagnetic behavior.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Concerning the impregnated metals on the ZSM-5 catalyst, more intense investigation on the corresponding characteristic peaks has been conducted. As shown in Figure 1, new peaks appear in the Co/ZSM-5 catalyst at 2θ = 31.3, 36.8, 45, 59.4, and 65.3°, corresponding to the Co3O4 (JCPDS-42-1467) [14][15][16]. It can be observed that the characteristic peaks of Co3O4 at 2θ = 31.3 and 45°, overlap with the characteristic peaks of ZSM-5.…”
Section: Catalysts Characterizationsmentioning
confidence: 86%